Rotational self-diffusion in suspensions of charged particles: simulations and revised Beenakker–Mazur and pairwise additivity methods1. Issue 26 (14th July 2015) - Makuch, Karol; Heinen, Marco; Abade, Gustavo Coelho; Nägele, Gerhard
<x xml:space="preserve">Abstract</x> We present a comprehensive joint theory-simulation study of rotational self-diffusion in suspensions of charged particles whose interactions are modeled by the generic hard-sphere plus repulsive Yukawa (HSY) pair potential.